PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 4 BEBETIN KABUPATEN BULELENG - I Komang Muliantara (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2021)
This study aims to improve learning outcomes class V students. This research is classroom action research. Based on the results of initial observations, student learning outcomes are still low. This study uses the Cooperative Integrated Reading and Composition learning model. This research was conducted at SDN 4 Bebetin in fifth grade students with a total of 15 students, consisting of 3 male students and 12 female students. Based on the results of the study, there was an increase in student learning outcomes from cycle I to cycle II. This is evidenced in the first cycle obtained 6 students (40%) who have completed and 9 students (60%) have not completed with an average value of 67. Cycle II increased to 12 students (87%) completed and 3 students (13%) incomplete with an average score of 89. From the results of cycle I and cycle II, it can be concluded that the application of the CIRC learning model can improve learning outcomes fifth grade students at SDN 4 Bebetin, Buleleng Regency.